Interpersonal perception and interpersonal spin. Issue 3 (9th October 2020) - Clegg, Kayleigh‐Ann; Moskowitz, D. S.; Miners, Christopher T. H.; Andrevski, Goce; Sadikaj, Gentiana; Zuroff, David C.
Abstract: Introduction: Interpersonal spin is an indicator of intraindividual variability in social behavior. Spin is positively related to Neuroticism and is maladaptive, with well‐documented deleterious effects on social functioning. The perceptual processes associated with spin and how spin emerges are less well‐understood. The present research examines the interpersonal perception of individuals with higher spin and tests whether these perceptual processes explain the association of spin with Neuroticism. Method: 267 students participated in a 20‐day event contingent recording procedure, reporting on social interactions via mobile application. Participants' perceptions of others' behavior, their own affect, and their own behavior were measured within and across interactions. Results: We examined the affective and behavioral responses of individuals with higher spin to perceptions of others' behaviors. Individuals with higher spin showed greater affective and behavioral reactivity to perceptions of others' communal (agreeable‐quarrelsome) behavior. Neuroticism predicted greater affective reactivity (i.e., steeper slopes between event‐level perceived communion and negative affect), which in turn predicted higher spin. Conclusions: Individuals with higher spin may have an interpersonal style characterized by greater reactivity to perceptions of others' communal behavior. These individuals' behavioral lability may reflect underlying emotional dysregulation. These processes may ultimately interfere with the formation and maintenance of social bonds.